2019
DOI: 10.1002/ecs2.2929
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐fire vegetation drives post‐fire outcomes in sagebrush ecosystems: evidence from field and remote sensing data

Abstract: Understanding the factors that influence vegetation responses to disturbance is important because vegetation is the foundation of food resources, wildlife habitat, and ecosystem properties and processes. We integrated vegetation cover data derived from field plots and remotely sensed Landsat images in two focal areas over a 37-yr period to investigate how historical changes to community composition influence contemporary responses of vegetation to fire in sagebrush ecosystems in the Great Basin. Our objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 98 publications
(230 reference statements)
0
14
0
Order By: Relevance
“…Exotic annual grass invasions rapidly altered disturbance characteristics, as has been observed by others (e.g., Bradley et al, 2018) and documented here as a fourfold increase in wildfire occurrence probabilities when exotic annual cover was greater than 10%, which can trigger abrupt shifts in ecosystem states and create novel environments that are maintained by new sets of legacies and reinforcing feedbacks. While ecosystem trajectories varied widely after wildfires, mainly due to vegetation composition and other site conditions (Figure 5; Barker et al, 2019), we found that enhanced rates of exotic annual growth generally occurred until about 20 years after fire and then increased at a decreasing rate thereafter. Individual fires events (on average) resulted in an 5% increase in exotic annual cover over a 40-year period, underscoring the role wildfires have on perpetuating the annual grass-fire cycle.…”
Section: Historical Spread and Drivers Of Exotic Annual Grass Covermentioning
confidence: 71%
“…Exotic annual grass invasions rapidly altered disturbance characteristics, as has been observed by others (e.g., Bradley et al, 2018) and documented here as a fourfold increase in wildfire occurrence probabilities when exotic annual cover was greater than 10%, which can trigger abrupt shifts in ecosystem states and create novel environments that are maintained by new sets of legacies and reinforcing feedbacks. While ecosystem trajectories varied widely after wildfires, mainly due to vegetation composition and other site conditions (Figure 5; Barker et al, 2019), we found that enhanced rates of exotic annual growth generally occurred until about 20 years after fire and then increased at a decreasing rate thereafter. Individual fires events (on average) resulted in an 5% increase in exotic annual cover over a 40-year period, underscoring the role wildfires have on perpetuating the annual grass-fire cycle.…”
Section: Historical Spread and Drivers Of Exotic Annual Grass Covermentioning
confidence: 71%
“…Non‐native cheatgrass ( Bromus tectorum ) has steadily invaded sagebrush ecosystems for decades and, as a fire‐prone species, creates a cheatgrass–wildfire cycle. In this cycle, degraded sagebrush systems are susceptible to invading cheatgrass, which increases wildfire frequency, further facilitating cheatgrass establishment; this process often leads to human interventions in the form of extensive and expensive restoration efforts (Barker et al., 2019; Brooks et al., 2004; Chambers et al., 2014). Sagebrush restoration techniques include protecting native plant communities, preventing non‐native invasion, and restoring degraded areas (Chambers et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Federal land managers must also understand the impact of allowable use (i.e., grazing policy) and budgets in the development of long-term management plans. The impacts of abrupt disturbances such as fire, industrial development, and vegetation treatments on rangeland condition have been relatively well documented [4,12]. However, spatially explicit data of projected climate impacts is often lacking, constraining the prioritization of areas for climate adaptation practices [13].…”
Section: Introductionmentioning
confidence: 99%